2010
DOI: 10.1192/bjp.bp.109.072504
|View full text |Cite
|
Sign up to set email alerts
|

Early intervention in panic: pragmatic randomised controlled trial

Abstract: People presenting with subthreshold and mild panic disorder benefit from this brief intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 23 publications
(27 reference statements)
1
22
0
Order By: Relevance
“…For study design and intervention, our study is comparable with the trial of Meulenbeek et al [10]. That study found a moderate effect size of d =0.68 for the face-to-face group course Don’t Panic, an intervention with similar content to Don’t Panic Online.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…For study design and intervention, our study is comparable with the trial of Meulenbeek et al [10]. That study found a moderate effect size of d =0.68 for the face-to-face group course Don’t Panic, an intervention with similar content to Don’t Panic Online.…”
Section: Discussionsupporting
confidence: 82%
“…Research indicates that it is also possible to prevent or delay the onset of clinical PD in people with subclinical panic symptoms [9,10]. A recent study showed that a group intervention involving primarily cognitive behavioral therapy effectively reduced symptoms in subclinical cases of PD, as well as in relatively mild cases [10]. This group course, called Don’t Panic, could also be acceptable from a cost-effectiveness point of view [11].…”
Section: Introductionmentioning
confidence: 99%
“…The benefit of early intervention and prevention was highly valued for individuals with subthreshold GAD and other subthreshold psychiatric syndromes [16,67,68]. Clinical trials examining people with various types of subthreshold anxiety confirm this benefit.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it would be important to identify people at high risk or in the early stages of psychosis, given that preliminary data have suggested that low doses of atypical antipsychotics associated with psychosocial interventions may delay the onset of psychosis in some individuals [63], and that early treatment with atypical antipsychotics may reduce the risk of transition to psychosis [64]. In addition, psychosocial interventions such as cognitive behavioral therapy and family interventions as well as close monitoring may be safer, more acceptable and more effective for at least a subgroup of patients in the early stages of psychosis [65], whereas patients with severe psychopathology at onset may benefit from an early intervention with low doses of second-generation antipsychotics [66]. The role of psychotherapy in its different forms should be better investigated in relation to DUP/DUI, in order to detect potential differences in efficacy between medications and psychotherapy or even against combined treatments.…”
Section: Resultsmentioning
confidence: 99%